Network Pharmacology-Based Evaluation of Sungkai (Peronema canescens J.) Leaf Bioactive Compounds as Potential Therapeutics for Cervical Cancer - Ratih Dyah Puspitasari (Jurnal Sains dan Terapan Kimia, 2026)
Cervical cancer continues to pose a significant public health challenge, especially in low- and middle-income countries, largely due to persistent Human Papillomavirus (HPV) infection and the limited efficacy and safety of current therapies. Although flavonoid-based anticancer agents such as jaceosidin have shown anticancer activity, their clinical use is limited by low bioavailability and insufficient clinical evidence, underscoring the need for safer, more effective therapeutic options. This study utilized in silico and network pharmacology methods to assess bioactive compounds from Sungkai leaves (Peronema canescens J.). Seven peronemin derivatives were evaluated for drug-likeness, toxicity, and anticancer potential through ADMET predictions, bioactivity profiling, and protein target identification. The findings demonstrated that peronemin C1 and D1 possess activity against cervical cancer cell lines and exhibit favorable pharmacokinetic properties. Network pharmacology analysis identified 115 cancer-associated targets, with STAT3 identified as a central hub regulating cell proliferation, apoptosis, and inflammatory signaling. Functional analyses further indicated that peronemin compounds modulate key oncogenic pathways, supporting their multitarget potential. Collectively, these results indicate that peronemin compounds from Sungkai leaves, particularly C1 and D1, are promising candidates for the development of cervical cancer therapies targeting STAT3.